Ketahanan Lapangan Padi Gogo terhadap Infeksi Curvularia oryzae - Muhammad Taufik; Asniah .; Syair . (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Southeast Sulawesi is known to have a wide varieties of local cultivars of upland rice. Unfortunately, resistance of those local cultivars of upland rice to Curvularia oryzae, one of the most important pathogen in upland rice cultivation, has not been reported. Resistance evaluation conducted in the field showed that local cultivars (Pae Kori, Pae Endokadia, and Pae Enggalaru) have high level of resistance, developing lines B10580E and B11580E have moderate resistance, whereas B11577E and TB368B lines were susceptible to C. oryzae infection.Key words: Curvularia oryzae, disease resistance, upland rice